Valentin Vodnik, The Illyrian Odes, and Political Censorship - Dović, Marijan (Slavia Centralis, 2024)
This article examines the first serious conflict between Slovenian poetry and the imperial authorities in the early 19th century using the example of two “Illyrian” odes by Valentin Vodnik. His “Ilirija Revived”, which was published during the French rule, brought serious problems for Vodnik after the restoration of Habsburg power in Carniola as he was accused of “Francophilia”. Following the Emperor’s decision, he was forced to retire and his poem remained banned for several decades. The present article outlines the dynamics of Vodnik’s relationship with the authorities and explains in more detail how and why he was subjected to political censorship.